Sustainable biochar to mitigate global climate change - Woolf, Dominic; Amonette, James E.; Street-Perrott, F. Alayne; Lehmann, Johannes; Joseph, Stephen (Nature communications, 2010)
Production of biochar (the carbon (C)-rich solid formed by pyrolysis of biomass) and its storage in soils have been suggested as a means of abating climate change by sequestering carbon, while simultaneously providing energy and increasing crop yields. Substantial uncertainties exist, however, regarding the impact, capacity and sustainability of biochar at the global level. In this paper we estimate the maximum sustainable technical potential of biochar to mitigate climate change. Annual net emissions of carbon dioxide (CO 2 ), methane and nitrous oxide could be reduced by a maximum of 1.8 Pg CO 2 -C equivalent (CO 2 -C e ) per year (12% of current anthropogenic CO 2 -C e emissions; 1 Pg=1 Gt), and total net emissions over the course of a century by 130 Pg CO 2 -C e , without endangering food security, habitat or soil conservation. Biochar has a larger climate-change mitigation potential than combustion of the same sustainably procured biomass for bioenergy, except when fertile soils are amended while coal is the fuel being offset. The storage in soils of biochar, the product of biomass pyrolysis, has been proposed as an attractive option to mitigate climate change. Amonette and co-workers model the potential impact of biochar and find that it could eliminate more carbon from the atmosphere than using the same biomass for biofuel.